Chemometric research of minerals and trace elements in selected malaysian local fruits using inductively coupled plasma optical emission spectroscopy (ICP-OES) - Badarusham K.; Sabri N.E.; Salvamani S.; Hassan M.S.; Hassan Z.; Hashim R. (Blue Eyes Intelligence Engineering and Sciences Publication, 2024)
Indexed by Scopus